Vocal criticism according to Ibn Al-Sayyid Al-Batalyusi: Achieving hamzah and alleviating it as an example - Al-Aqaili, Ammar; Naseem , Batoul (Al-Adab Journal, 2024)
Among the phenomena of vocal criticism according to Ibn Al-Sayyid Al-Batalyusi (521 AH), is what is related to reducing the hamza and achieving it, It is one of the common and well-known phenomena in Arabic dialects, as Al-Batalyusi followed the statements of linguists regarding this phonetic phenomenon and dealt with it with criticism, In doing so, he relied on the evidence of the linguistic industry, namely: (listening, analogy, and consensus). Al-Batalyusi developed for himself an objective, fair, and moderate critical approach, far from fanaticism and blind bias, and his critical character was surrounded by caution against censure or sarcasm, And similar expressions that others often use, and most of his vocal critical opinions agreed with what was approved by the modern vocal lesson, And similar expressions that others often use, and most of his opinions agreed with his choice of making the hamza easier in some slurred words. It was consistent with the vision of the modern phonetic approach, which considered the hamza to be one of the most difficult letters when pronouncing, so it was made simplified in order to reduce it and save muscular effort in speech.